Selection on parental performance opposes selection for larger body mass in a wild population of blue tits. (1st March 2017) - Thomson, Caroline E.; Bayer, Florian; Crouch, Nicholas; Farrell, Samantha; Heap, Elizabeth; Mittell, Elizabeth; Zurita‐Cassinello, Mar; Hadfield, Jarrod D.
Abstract: There is abundant evidence in many taxa for positive directional selection on body size, and yet little evidence for microevolutionary change. In many species, variation in body size is partly determined by the actions of parents, so a proposed explanation for stasis is the presence of a negative genetic correlation between direct and parental effects. Consequently, selecting genes for increased body size would result in a correlated decline in parental effects, reducing body size in the following generation. We show that these arguments implicitly assume that parental care is cost free, and that including a cost alters the predicted genetic architectures needed to explain stasis. Using a large cross‐fostered population of blue tits, we estimate direct selection on parental effects for body mass, and show it is negative. Negative selection is consistent with a cost to parental care, mainly acting through a reduction in current fecundity rather than survival. Under these conditions, evolutionary stasis is possible for moderately negative genetic correlations between direct and parental effects. This is in contrast to the implausibly extreme correlations needed when care is assumed to be cost‐free. Thus, we highlight the importance of accounting correctly for complete selection acting on traits across generations.